STRATEGI PENGEMBANGAN USAHA PERSUTERAAN ALAM DI KABUPATEN SUKABUMI, PROPINSI JAWA B - Wijayanto, Nurheni; Fauziah, Eva (Jurnal Manajemen Hutan Tropika, 2012)
The striving of nature silk in Kabupaten Sukabumi keeps decreasing whereas, market opportunity and potential for nature is good, for this time being. For knowing development strategic of striving nature silk correctly, it need to be done an aprroachment system of replacement SWOT analysis  (strategis analysis) and ISM (interpretative Structural Modelling) technique (structural analysis). This research will identify internal and external factor and produce structural models.The most powerful factor that influence the striving of nature silk is nature condition (climate, soil and topography).  The weakness factor are limited capital and access.  As opportunity element factor and treatment of cocoon needs still high and germ and disease of murbei leaves also silk worm.Prosperity of nature silk worm influence a lot of society sector especially farmer.  In way to make it success needs very qualified human resources, an expert on this work and good management.  Hoped with fulfilled need, will solved a lot of obstructions one of them is limited capital and access.  The purpose of this program as good as possible is for increasing nature silk work.  Involved all sorts of institution to realize this aim will be need, one of them is Forestry Department which will decide fact in striving of nature silk.